Faculty of Business and Management (FBM), UiTM, successfully organized industry talk on corporate finance. - UiTM, Faculty of Business and Management (UiTM, 2023)
The Faculty of Business and Management (FBM), UiTM, successfully organized an industry talk on corporate finance to enhance students’ knowledge and practical skills in financial management.